Cyatta abscondita: Taxonomy, Evolution, and Natural History of a New Fungus-Farming Ant Genus from Brazil - Sosa-Calvo, Jeffrey; Schultz, Ted R.; Brandao, Carlos R. F.; Klingenberg, Christiana; Feitosa, Rodrigo M.; Rabeling, Christian; Bacci, Maurício [UNESP]; Lopes, Caue T.; Vasconcelos, Heraldo L. (Public Library Science, 2013)
Cyatta abscondita, a new genus and species of fungus-farming ant from Brazil, is described based on morphological study of more than 20 workers, two dealate gynes, one male, and two larvae. Ecological field data are summarized, including natural history, nest architecture, and foraging behavior. Phylogenetic analyses of DNA sequence data from four nuclear genes indicate that Cyatta abscondita is the distant sister taxon of the genus Kalathomyrmex, and that together they comprise the sister group of the remaining neoattine ants, an informal clade that includes the conspicuous and well-known leaf-cutter ants. Morphologically, Cyatta abscondita shares very few obvious character states with Kalathomyrmex. It does, however, possess a number of striking morphological features unique within the fungus-farming tribe Attini. It also shares morphological character states with taxa that span the ancestral node of the Attini. The morphology, behavior, and other biological characters of Cyatta abscondita are potentially informative about plesiomorphic character states within the fungus-farming ants and about the early evolution of ant agriculture.